2012
DOI: 10.1155/2012/371584
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuritis in an Adult Patient with Chickenpox

Abstract: Central nervous system involvement in a patient with primary infection with Varicella zoster virus is rare, especially in the immunocompetent adult. In particular, isolated optic neuritis has been described in a small number of cases. The authors present a case of optic neuritis in an immunocompetent patient. A 28-year-old woman presented to the emergency room with a history of headaches during the previous week, without visual symptoms. The examination was unremarkable, except for a rash suggestive of chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…2 While direct viral invasion may play a role in rare parainfectious cases, the majority are believed to reflect postinfectious autoimmunity. There is no clear rule for the latency between viral infection and secondary ON, but in reviewing several cases in the literature, we found latencies of 2 days, 3 2 weeks, 4 and 4 weeks. 5 The range of latencies one could expect following COVID-19 infection could well be longer than with other infections, but as a rule, we felt that latencies of 3 months or longer put into question a true association, given the high frequency of COVID-19 infection in the population.…”
Section: Optic Neuritismentioning
confidence: 57%
“…2 While direct viral invasion may play a role in rare parainfectious cases, the majority are believed to reflect postinfectious autoimmunity. There is no clear rule for the latency between viral infection and secondary ON, but in reviewing several cases in the literature, we found latencies of 2 days, 3 2 weeks, 4 and 4 weeks. 5 The range of latencies one could expect following COVID-19 infection could well be longer than with other infections, but as a rule, we felt that latencies of 3 months or longer put into question a true association, given the high frequency of COVID-19 infection in the population.…”
Section: Optic Neuritismentioning
confidence: 57%
“…ARN generally involves immunocompetent patients, starts peripherally, and spreads centripetally ( 12 ). The clinical diagnosis of ARN is based on the diagnostic criteria established by the American Uveitis Society, which consists of: ( 1 ) one or more discrete foci of peripheral retinal necrosis, ( 2 ) occlusive retinal vasculitis with arteriolar involvement, ( 3 ) prominent inflammation in the anterior and posterior chambers, ( 4 ) circumferential disease spread, and ( 5 ) rapid progression of disease in the absence of treatment ( 13 ). ARN almost always occurs with reactivation of a herpetic latent virus, nonetheless, primary herpes infections may cause a clinical picture resembling ARN.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases in adults have also been reported. Azevedo et al 14 and Galbussera et al 15 reported cases of optic neuritis following chicken pox in adults. Ihanamaki et al 16 reported a case of parainfectious bilateral optic neuritis associated with echoviral meningitis in an adult patient.…”
Section: Discussionmentioning
confidence: 99%